2015
DOI: 10.1093/aje/kwu467
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Interviewer-Administered and Automated Self-Administered 24-Hour Dietary Recalls in 3 Diverse Integrated Health Systems

Abstract: Twenty-four-hour dietary recalls provide high-quality intake data but have been prohibitively expensive for large epidemiologic studies. This study's goal was to assess whether the web-based Automated Self-Administered 24-Hour Recall (ASA24) performs similarly enough to the standard interviewer-administered, Automated Multiple-Pass Method (AMPM) 24-hour dietary recall to be considered a viable alternative. In 2010-2011, 1,081 adults from 3 integrated health systems in Detroit, Michigan; Marshfield, Wisconsin; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(163 citation statements)
references
References 13 publications
8
146
3
2
Order By: Relevance
“…In addition, the ASA24 requires access to high-speed internet, which may limit its use in certain circumstances, although this is likely to be less of an issue moving forward with continued advances in technology. A large community-based study conducted in adults with known Internet access showed that participants had high completion rates of 2 nonconsecutive recalls with the use of either interviewer-administered AMPM or ASA24 recalls, and that respondents overwhelmingly preferred the ASA24 to interviewer-administered recalls (27). This suggests that the ASA24 may be viable for use in a range of studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ASA24 requires access to high-speed internet, which may limit its use in certain circumstances, although this is likely to be less of an issue moving forward with continued advances in technology. A large community-based study conducted in adults with known Internet access showed that participants had high completion rates of 2 nonconsecutive recalls with the use of either interviewer-administered AMPM or ASA24 recalls, and that respondents overwhelmingly preferred the ASA24 to interviewer-administered recalls (27). This suggests that the ASA24 may be viable for use in a range of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the system the tools require more or less input from the user. On the whole, users prefer the new technology approach to the traditional interviewer or paper-based systems (6,(13)(14)(15)(16) . However, this may depend on technology readiness and experience with online systems (1,16) .…”
Section: Why Do We Need New Methods and What New Methods Are Available?mentioning
confidence: 99%
“…Some studies have shown that, compared with the traditional interview, web-based 24-h recall generates equivalent results with a reduced precision for some nutrients [6,19,20]. However, the preference for the web-based version was highlighted by many researchers.…”
Section: Introductionmentioning
confidence: 99%